FEMALE FERTILITY THERAPIES (2017)
Described are novel female fertility therapies. A first aspect of the invention is directed to therapies that include FSH lowering methodologies to prevent and/or treat egg infertility. A second aspect of the invention is directed to agents that bind to activin, bind to receptors that bind activin, or that otherwise disrupt activin signaling (collectively referred to herein as "activin pathway modifier agents" or "APM agents") and methods of utilizing these agents to prevent and/or treat egg infertility. A third aspect of the invention is directed to methods of administering an effective amount of an APM agent to a subject to increase oocyte yield and/or ovarian reserve. All three aspects of the invention may be used in humans and in animals. Additional aspects of the invention include therapeutic drug kits for treatment of humans and animals based on the methodologies described above.